Chemical composition of Pacific manganese nodules and crusts analyzed at Scripps Institution of Oceanography using atomic absorption spectrophotometry (AAS) - Mary B Fisk; Jane Z Frazer (PANGAEA, 2022)
16 manganese nodules and crusts from 11 sites in the Pacific Ocean were analyzed at Scripps Institution of Oceanography using atomic absorption spectrophotometry (AAS). Samples were ground to < 74 microns, pressed into pellets and dried at 110 Degrees Centigrade.